Rasa Koherensi Terkait Pekerjaan di Kalangan Dosen dan Staf Pendidikan - Wahyu Agung Budi Alamsyah; Andik Supriyatno; Muhammad Rafli Aidillah; Muhammad Henry Gunawan (Journal of Telenursing (JOTING), 2026)
This study aimed to measure the level of Work-SOC (Sense of Coherence at work) among lecturers and administrative staff at a private health-focused higher education institution in Samarinda, East Kalimantan, and to examine whether there were significant differences between the two groups regarding this measure. A descriptive-analytic design with a cross-sectional approach was employed. The results showed that the majority of respondents fell into the low category (56.9%), with "meaningfulness" being the weakest dimension (72.2% low), followed by "comprehensibility" (69.4% low) and "manageability" (65.3% low). Administrative staff obtained a significantly higher total Work-SOC score (M=36.12, SD=6.984) compared to lecturers (M=33.21, SD=4.991), t(70)=-2.042, p=0.045. This pattern suggests that the broader and less defined workload of lecturers is likely a source of low work coherence, with meaningfulness being the component requiring the most attention. In conclusion, the institution needs to develop evidence-based human resource well-being programs that go beyond merely adding facilities; instead, they should restructure workloads, strengthen leadership support, clarify career paths, and—importantly—revitalize the sense of meaning in academic work. Keywords: Workload, Lecturers, Work Well-being, Higher Education, Sense of Coherence